Ease Of Use Dan Trust Terhadap Purchase Intention Melalui Customer Satisfaction Pada Situs Web Tokopedia - Juliana Juliana*; Themmy Noval; Ira Brunchilda Hubner; Innocentius Bernarto (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2020)
ABSTRACTThis study aims to analyze the ease of use variable is a positive predictor of purchase intention, to analyze the ease of use variable is a positive predictor of customer satisfaction, to analyze whether trust is a positive predictor of purchase intention, to analyze whether trust is a positive predictor of customer satisfaction and to analyze whether customer satisfaction is a positive predictor of purchase intention. The population used in this study were all users of web sites or Tokopedia applications in Indonesia. Considering the number of web site users or Tokopedia applications, the researchers took samples from the population to be respondents in the study. The research sample was collected from customers who use the Tokopedia website or application and are domiciled in the Greater Jakarta area. Hypothesis testing is done with the main data of 300 respondents. The technique in sampling in this study uses probability sampling techniques. The type of probability sampling used is the simple random sampling method. Data analysis tools were analyzed using SPSS ver 23 to measure the ease of use and trust variables of purchase intention through customer satisfaction in the Tokedia application and found that ease of use is a positive and significant predictor of purchase intention, ease of use is a positive predictor and significant to customer satisfaction, trust is a positive and significant predictor of purchase intention, trust is a positive and significant predictor of customer satisfaction, customer satisfaction is a positive and significant predictor of purchase intention.Keywords : ease of use, trust, purchase intention, customer satisfaction